(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This manuscript studies some unique and common fixed point results in the context of bi-complex valued control metric space(BVCMS) using rational-type inequalities. The presented work explains the idea of BVCMS and then shows the necessary criteria for a pair of contractive type mappings in this space to have common fixed points. To show how applicable our results are, we also give an example. Finally, the existence of solutions of a system of fractional differential equations has been studied using the obtained results.